Approximate Fundamental Frequency of a Circular Mindlin Plate by Morley's Formula - Altekin, Murat (AMER INST PHYSICS, 2019)
Fundamental frequency of a shear deformable circular plate with uniform thickness was obtained using the static deflections. First, the plate was loaded by a uniform transverse pressure which represents the weight of the plate. Next, the plate was discretized into four-noded isoparametric quadrilateral elements, and the finite element method was applied to find the nodal deflections. Finally, the centroidal deflection for each element was computed, and the Morley's formula was used to approximate the fundamental frequency of the plate. Convergence and comparison studies were performed for h-refinement.
Keywords: Mathematics; Physics